Clinical Profile of Patients Undergoing Temporary Transvenous Pacing in a Tertiary Cardiac Care Centre in Nepal - Sharma, Manju; Jha, Sunil C; Sayami, Arun; Gajurel, Ratna M; Poudel, Chandra M; Khanal, Rajaram; Pathak, Surya R; Thapa, Shovit; Adhikari, Suman; Yadav, Vijay (Journal of Institute of Medicine Nepal, 2020)
Introduction Temporary transvenous pacemaker insertion is an emergency lifesaving procedure for patients with hemodynamically unstable and life-threatening bradyarrythmias. The aim of this study was to analyze demographics, indications, route of insertion and complications in patients undergoing temporary transvenous pacemaker implantation. Methods This was a retrospective observational study conducted at a tertiary-care center in Nepal. The hospital records of patients who had undergone temporary transvenous pacemaker implantation between July 2015 and June 2019 were reviewed. Results A total of 343 patients with mean age of 65.52±16.09 years received temporary transvenous pacing. Out of these 205 (59.8%) were males. Greater proportion of patients were between the age group of 70-80 years (n=76, 22.2%). Hypertension (n=97, 28.3%) was the most common comorbidity noted. The most common indication for temporary pacing was symptomatic complete heart block 165 (59.6%). Total of 288 (84%) patients received permanent pacemakers while 55(16%) had reversible cause so TPI was removed. Right Femoral vein was the most common (99%) venous access site. Among the 343 patients, complications were observed in 29 (8.4%) of cases during and after the temporary transvenous pacemaker insertion. The overall mortality stood low at 2% (n=7). Conclusion Temporary transvenous pacemaker insertion is required in elderly population presenting with bradyarrythmias and occasionally in acute myocardial infarction presenting with bradyarrythmias as complication. Temporary pacemaker insertion was overall a safe procedure with infrequent serious complications; however, strategies to avoid and alleviate such complications (RV perforation) should be sought and implemented.